2019
DOI: 10.29333/iji.2019.12434a
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between Writing Anxiety Dimensions and Writing Goal Orientation among Iraqi EFL Undergraduates

Abstract: This study aimed to examine the relationships between facilitating writing anxiety (FWA), debilitating writing anxiety (DWA), mastery-approach goal (MAG), performance-approach goal (APPG) and performance-avoidance goal (AVOG). In total, 300 Iraqi undergraduate students participated in the study. A quantitative approach was applied in particular correlational design. Two questionnaires were utilized for data collection: The Second Language Writing Anxiety Inventory (SLWAI) and Achievement Goal Questionnaire (AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Regression and correlation analysis are used to answer the research objectives in this study. According to Sabti et al (2019), it is possible to decide whether a correlation is strong or weak and this can be done by referring to the table by Guildford Rules of Thumb. Table 5 shows the level of correlation as according Guildford Rule of Thumb: For the analysis of reward and enjoyment, it can be found that the correlation level is strong.…”
Section: Resultsmentioning
confidence: 99%
“…Regression and correlation analysis are used to answer the research objectives in this study. According to Sabti et al (2019), it is possible to decide whether a correlation is strong or weak and this can be done by referring to the table by Guildford Rules of Thumb. Table 5 shows the level of correlation as according Guildford Rule of Thumb: For the analysis of reward and enjoyment, it can be found that the correlation level is strong.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed a significant negative association between the sub-constructs of writing anxiety and all three measures in both types of writing. Sabti et al (2019) conducted research on the relationships between two dimensions of L2 writing anxiety, namely facilitating and debilitating anxiety, and the constructs of writing goal orientation. Their results demonstrated positive relationships between mastery-and performance-approach goals and facilitating writing anxiety, and a negative relationship between a combination of debilitating writing anxiety and performance-avoidance goal, and the factors of mastery-and performance-approach goal and facilitating writing anxiety.…”
Section: The Association Of L2 Writing Anxiety With Various Constructsmentioning
confidence: 99%
“…The above-mentioned literature providing valuable data on mostly the adverse and debilitating influence of anxiety on L2 students' writing ability appears to involve abundant research, yet further studies are still needed for several reasons. First, the relevant research demonstrates a prevailing tendency towards quantitative methodology, drawing predominantly on descriptive or correlational data (Heiderzadi et al, 2022;Keyvanoğlu & Atmaca, 2023;Kırmızı & Kırmızı, 2015;Li, 2022;Mulyono et al, 2020;Quvanch & Na, 2022;Sabti et al, 2019;Woodrow, 2011). Qualitative and mixed-method studies, which may contribute to a more profound understanding of this skill-specific and highly personalized type of anxiety, are relatively few (Genç & Yaylı, 2019;Rabadi & Rabadi, 2020).…”
Section: Descriptive Studies On L2 Writing Anxietymentioning
confidence: 99%
“…It is said that the model's prediction is better the higher the correlation coefficient [16], a coefficient <0.40 has low correlation, coefficients between 0.40-0.70 have normal correlation, coefficients >0.70 and above have high correlation. It is stated that it indicates good performance results [4,27,28,29]. Since MAE and RMSE, which are one of the most frequently used error measures among estimation methods, are error measures, the performance of the model will be higher if they take low values close to zero [16,30], and it is better to evaluate them together, but not limited to them.…”
Section: Weka Decision Treesmentioning
confidence: 99%